THE RELATIONSHIP BETWEEN CLEAN WATER SOURCES AND PERSONAL HYGIENE WITH THE INCIDENCE OF DIARRHOEAL DISEASE IN PUBLIC SCHOOLS 101826 KUTALIMBARU, PANCUR BATU SUB-DISTRICT, DELI SERDANG DISTRICT - Sianturi, Anggina Cucu Khetri; Nanda, Meutia; Saragih, Eka Fitria; Dalimunthe, Halimatus Sa’diyah; Sinambela, Nur Delina (HEARTY, 2025)
Diarrhoeal diseases in the Medan City area, especially in Deli Serdang Regency, recorded 25934 cases while in 2023 there was a very significant increase of 33,771 cases of diarrhoea recorded at the Central Statistics Agency (BPS). The purpose of this study was to determine whether there is a relationship between personal hygiene and clean water sources. This research method uses Quantitative methods conducted through analytical surveys. The design used in this study was a cross-sectional survey. This research was conducted at SD Negeri 101826. The population of this study was 233 students, while the sample used was 70 students. The results showed that there was a significant relationship between personal hygiene (hand hygiene) and the incidence of diarrhoeal disease (p-value=0.001), there was a significant relationship between snacking habits and the incidence of diarrhoeal disease (p-value=0.001), there was no significant relationship between water sources and the incidence of diarrhoeal disease (p- value=0.127). Based on the above conclusions, it is expected that students of SD Negeri 101826 Tuntungan Pancur Batu can pay attention to personal hygiene both the habit of washing hands using soap after eating, drinking and after bathing to prevent the occurrence of diarrhoeal disease.